The History and Science of the Manhattan Project, Second Edition. Issue 9 (25th August 2014) - Mihailidis, Dimitris
Abstract : The History and Science of the Manhattan Project, Second Edition. Cameron Reed B., Springer‐Verlag, NY, 2014. 472 pp. Price: $39.99. ISBN 978‐3‐642‐40296‐8 (hardcover).